Direct conversion of CO2 to meso/macro-porous frameworks of surface-microporous graphene for efficient asymmetrical supercapacitors. Issue 44 (1st November 2017) - Chang, Liang; Stacchiola, Dario J.; Hu, Yun Hang
Abstract : Meso/macro-porous frameworks of surface-microporous graphene are synthesized for excellent asymmetrical AC//MFSMG capacitors. Abstract : CO2 conversion to useful materials is the most attractive approach to control its content in the atmosphere. An ideal electrode material for supercapacitors should possess suitable meso/macro-pores as electrolyte reservoirs and rich micro-pores as places for the adsorption of electrolyte ions. Herein, we designed and synthesized such an ideal material, meso/macro-porous frameworks of surface-microporous graphene (MFSMG), from CO2 via its one-step exothermic reaction with potassium. Furthermore, the MFSMG electrode exhibited a high gravimetric capacitance of 178 F g −1 at 0.2 A g −1 in 2 M KOH and retained 85% capacitance after increasing current density by 50 times. The combination of the MFSMG electrode and the activated carbon (AC) electrode constructed an asymmetrical AC//MFSMG capacitor, leading to a high capacitance of 242.4 F g −1 for MFSMG and 97.4 F g −1 for AC. With the extended potential, the asymmetrical capacitor achieved an improved energy density of 9.43 W h kg −1 and a power density of 3504 W kg −1 . This work provides a novel solution to solve the CO2 issue and creates an efficient electrode material for supercapacitors.